The Role Of Mediating Resistance To Change In The Influence Of The Digital Divide On Lecturers' Work Results During The Covid-19 Pandemic In Indonesian Universities - Sahputri, Rindi Ardika Melsalasa; Sihombing, Septiana; Eva Rini, Lamia; Agustia Salsabila, Dia (Fakultas Ekonomi Universitas Tjut Nyak Dhien Medan, 2025)
Purpose – A dramatic technology-adopted change in the educational fields during the COVID-19 pandemic resulted in a digital divide among academics. This study aims to investigate the digital divide in the implementation of online learning in Indonesian public universities and its association with resistance to digital adoption and work-related outcomes during the pandemic. Novelty – The novelty of this study lies in the investigation of multilevel measure of digital divide which is linked to resistance to new adoption of online learning and work-related outcomes Method – The data was gathered from 155 lecturers across 15 universities. The analysis used hierarchical regression analysis and structural equation modelling to test the correlation patterns among dimensions of digital divide, resistance to change, and work-related outcomes. Findings – The results found that the digital divide has a strong relationship with lecturers’ resistance to change and work-related outcomes. A multidimensional model of the digital divide also had a patterned relationship with the multidimensional model of resistance to change, as well as resistance to change having specific relationships with lecturers’ work commitment, satisfaction and performance. Limitations and Implications – The limitation of this cross-sectional study conducted at only single point in time and limited sample size that cannot fully cover all of the region of Indonesian lecturers living in remoted areas especially in East Indonesia reduce the generalisability of ths study and reduce the causative nature of the analysis. However, This study contributes to our understanding of employees’ attitudes toward change during the pandemic, particularly in relation to the digital divide, resistance to change, and work-related outcomes.